2017
DOI: 10.1007/s40618-017-0615-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of point-of-care 3-hydroxybutyrate testing in patients with type 2 diabetes undergoing coronary angiography

Abstract: PurposeKetone bodies, 3-hydroxybutyrate (3BOHB), and acetoacetate derive from increased free fatty acid beta-oxidation, thus reflecting marked insulin deprivation with or without decompensated diabetes. Objectives of this study were (1) to determine circulating levels of 3BOHB in patients with and without type 2 diabetes (T2DM), before and after an elective coronary angiography; (2) to detect 3BOHB modification during the procedure; (3) to study possible associations between 3BOHB and clinical parameters/outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Hence, the increased metabolism of ketones may play a part in the response to myocardial ischemia ( 21 ). Accumulating evidence has shown that the BHB level is increased in patients with heart failure ( 14 , 22 ), obese and/or T2DM ( 12 , 23 ). Of importance, with metabolic dysfunction as an inherent feature of the CAD pathophysiology, whether circulating BHB is increased in CAD remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the increased metabolism of ketones may play a part in the response to myocardial ischemia ( 21 ). Accumulating evidence has shown that the BHB level is increased in patients with heart failure ( 14 , 22 ), obese and/or T2DM ( 12 , 23 ). Of importance, with metabolic dysfunction as an inherent feature of the CAD pathophysiology, whether circulating BHB is increased in CAD remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…During perturbed tissue metabolism, an increase in BHB may help circumvent the metabolic malfunctions that directly contribute to disease pathophysiology ( 11 ). Recent studies have shown that BHB level was increased in a myriad of pathological conditions, such as type 2 diabetes mellitus (T2DM) ( 12 ), arrhythmogenic cardiomyopathy ( 13 ), and heart failure ( 14 ). In addition, it was reported that BHB was increased in patients with non-ST segment elevation acute coronary syndrome, which reflects the oxidative stress and hypoxic state that myocardial cells suffer.…”
Section: Introductionmentioning
confidence: 99%
“…The most robust evidence from a retrospective cohort study demonstrated that β-HDBA was independently and signi cantly associated with adverse cardiovascular events and therefore could serve as a novel biomarker predicting both survival and incidents of cardiovascular events in patients with hemodialysis [16]. Accumulating evidence has also shown that β-HDBA levels were elevated in patients with heart failure [14,21], obese and/or type 2 diabetes [12,22]. Of importance, with metabolic dysfunction as an inherent feature of the CAD pathophysiology, whether circulating β-HDBA is increased in CAD remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…When perturbed tissue metabolism happens, an increase in β-HDBA (ketone bodies) may help circumvent the metabolic malfunctions that directly contributes to disease pathophysiology [11]. Recent studies have showed that β-HDBA level was increased in a myriad of pathological conditions, including type 2 diabetes [12], arrhythmogenic cardiomyopathy [13] and heart failure [14]. In addition, it was reported that β-HDBA was elevated in non-ST segment elevation acute coronary syndrome patients, re ecting the oxidative stress and the hypoxic state that suffers the myocardial cells, which indicated that β-HDBA may have a great potential for early diagnosis of acute coronary syndrome [15].…”
Section: Introductionmentioning
confidence: 99%
“…The abnormal increase in the content of 3-hydroxybutyrate in the model group may be the result of the lack of insulin in the diabetic rats, which led to the compensatory increase to supply the energy required for physiological activities in the body. 102 …”
Section: Discussionmentioning
confidence: 99%